Different mr-proANP-release in High Volume High Intensity Interval Exercise and Continuous Exercise Regimens with Matched Mean Intensity: A Cross-over Design Study - Julian Eigendorf (Sapientia Publishing Group, 2020)
OBJECTIVES Prevalence and risk factors of arterial stiffness and diabetes can be improved through physical activity and exercise. Atrial natriuretic peptid (ANP) does impact vasodilation and lipid metabolism and thus is connected to both pathologies. To extend insights in ANP-release we measured mid regional-proANP (mr-proANP) in different exercise training protocols in rest and at cessation of exercise. We evaluated a high volume high intensity interval (HVHIT), high volume sprint interval training (HVSIT) and a continuous exercise (CE) regimen with matched mean intensity. METHODS Subjects completed HVHIT (30s interval/30s pause), HVSIT (6s interval /24s pause) and continuous exercise (CE) over 45 min, as well as an initial graded exercise test (GXT) to asses maximum power output (PmaxGXT). Intervals during HVHIT were set to 100% PmaxGXT, intervals during SIT were set to 250% PmaxGXT and load during CE was set to 50% PmaxGXT. HVHIT, HVSIT and CE sessions were initiated with a 10 min warm-up and concluded with a 10 min cool-down. Venous blood samples were drawn at rest and after cessation of exercise. RESULTS Δmr-proANP was significantly different (p=0.048; RM ANOVA) between the three different exercise regimens. Δmr-proANP during CE was 17.8 (±2.0) pmol*l-1, during HVHIT 22.5 (±4.5) pmol*l-1 and during SIT 24.5 (±7.8) pmol*l-1. [Δmr-proANP] was not correlated to absolute power during intervals, peak oxygen uptake or heartrate, but was significantly correlated to Δlactate. CONCLUSIONS We conclude that high intensity exercise causes a higher ANP-release than CE. This can be caused by the recurrent shift from relaxing and stressing of the heart muscle, which is known to trigger ANP-release. Other factors are likely to contribute to ANP-release.